Ações de educação permanente em saúde desenvolvidas por equipes de atenção básica em saúde - Raddatz, Michele (2014)
The Health System aims to qualitatively meet the health needs of the population. However, to accomplish this service, the Permanent Health Education, has been used as an essential tool since it allows joint attention, training, management and social control to face the problems of different levels of care, including the Attention Ladies in Health because of this, this research aims to characterize the professional teams of primary Health Care; identify actions EPS developed by professional teams of Primary Health Care; describe the concepts of professional teams from Primary Health Care on EPS; identify the perceptions that professional teams of Primary Health Care have over the actions of EPS; analyze the possibilities and limits of development of EPS in teams of Primary Care in Health. This is a qualitative, exploratory and descriptive survey of 19 professionals from two teams of the Family Health Strategy in a city in Rio Grande do Sul in the period March-May 2013. Production data was through interviews individual semi-structured, recorded and transcribed. The research corpus was subjected to qualitative analysis. The ethical principles were respected according to Resolution Nº 196/96 and 466/12. After thematic analysis revealed three categories with their respective subcategories: Conceptions of professionals about the Permanent Health Education; Shares of Continuing Education in Health developed by the teams and triggering changes in everyday services; and Possibilities for the development of Continuing Education in Health team (Potentiating the actions of Continuing Education in Health and Limits for the development of actions of Continuing Education in Health Factors team). From the data analysis it became clear that professionals understand the Permanent Health Education and Continuing Education; actions developed are essentially excluding Continuing Education staff meetings and that these changes actually trigger the services; brings as a factor hampering the development of actions of Continuing Education in Health mainly the lack of human resources, lack of motivation and encouragement, as well as lack of physical infrastructure and high demand leading to lack of time for the development of education actions. It is hoped that these findings will contribute to that teams can potentiate the actions that have been developing for Continuing Education in Health and the management as well as training contributes to this tool is used as a qualifier of health services.